Internet of Things enabled sedentary behaviour change in office workers: development and feasibility of a novel intervention (WorkMyWay) - Huang, Yitong (2020)
Sedentary behaviour (SB) without breaks is associated with adverse health outcomes. The prevalence of prolonged sitting at work among office workers makes a case for SB interventions to target this setting and population. Everyday mundane objects augmented with microelectronics and ubiquitous computing represent a novel mode of delivery for behaviour change interventions enabled by the Internet of Things (IoT). However, there is insufficient research to guide the design of interventions delivered with smart objects. This research addresses this gap by developing WorkMyWay, a workplace SB intervention delivered with IoT-enabled office objects (e.g. smart water bottles and cups), and evaluating its feasibility and acceptability in an 8-week “in-the-wild” study. This thesis made 4 contributions across the disciplines of behavioural medicine and human-computer interactions (HCI). The first contribution is the development of the WorkMyWay intervention, which is informed by findings from a systematic scoping review of prior research in this field (Chapter 3), a diary-probed interview study with 20 office workers (Chapter 4), and a series of technology audit, prototyping, human-centred design, and requirement engineering processes (Chapter 5). Findings from the feasibility study (Chapter 6) suggest that despite technical issues with the data connection, participants perceive high value of WorkMyWay in changing their SB. The intervention is potentially implementable in office-based workplaces, as long as connectivity issues are fixed. Recommendations are made on improvements and a series of future studies in accordance with the Medical Research Council’s guidance on complex intervention development and evaluation. Second, this thesis deepens the theoretical understanding of SB change, by following the Behaviour Change Wheel framework (including the COM-B model, theoretical domain framework, and taxonomies of Behaviour Change Techniques (BCT)) throughout intervention design and evaluation. The intervention contents are specified using the BCT taxonomies (Chapter 5) and informed by the first published COM-B analysis of office worker’s prolonged sitting behaviour at work (Chapter 4). This allows the feasibility study (Chapter 6) to contribute to theory development by matching the interview questions and psychological measures (e.g. strength of habit) with the BCTs (e.g. action planning, prompts and cues) and associated theoretical underpinnings (e.g. goal accessibility). It also allows implementation issues to be considered in light of how well those theories and theory-informed BCTs can work in real-life settings. Third, this thesis makes a methodological contribution by documenting an interdisciplinary approach to develop a digital behaviour change intervention and a model for applying and developing theories of behaviour change in the wild. This helps address the challenge identified in Chapter 3, by bridging the gap between HCI and behavioural medicine, and catalyse the process of feeding technological innovations downstream to health practice and intervention research. Fourth, this research contributes to the HCI literature by proposing a 2×2 matrix framework to guide the design of technology for sustainable behaviour change. On one hand, the framework unifies some of the existing visions and concepts about ubiquitous computing and applies them to the context of behaviour change, by considering the type of cognitive process (automatic versus reflective, based on the dual process model) through which a persuasive design influences the behaviour. For another, the framework considers the required dosage of their technology intervention to maintain the behaviour, or the distribution of changes between the physical world and the human cognition.